Voluntary agreements in environmental policy: Negotiating emission reductions - Dirk Schmelzer (Fondazione Eni Enrico Mattei (FEEM), 1997)
Voluntary agreements are an important environmental policy instrument. In the paper some examples are discussed and the structure and mechanisms of voluntary agreements are analyzed using a strategic game approach. In the simple strategic game with only one abatement technology, there is a unique subgame perfect equilibrium, making voluntary agreements one option of reaching an efficient emission level. However, this solution changes with the introduction of a continuum of emission levels. In the ultimatum bargaining game the emission level will always be higher than the efficient. This holds also for Nash's cooperative bargaining solution. Given bargaining cost on both sides and an exogenous probability for the negotiations to stop at a certain time, the state profits from low discounting, low bargaining cost and a high probability of breakdown.
Keywords: 330; Umweltschutz; Selbstverpflichtung; Spieltheorie; Verhandlungen; Theorie